Determination of physico-chemical properties and agricultural potentials of soils in Tembaro District, KembataTembaro Zone, Southern Ethiopia - Alemu Lelago; Tadele Buraka (Eurasian Journal of Soil Science, 2019)
The objectives of this study were to classify the soils of Tembaro district, and to identify its potentials for crop production. Five pits representing a pedon each were opened and profile in each pit was described for its morphological, physical and chemical characteristics according to standard procedures. A total of 20 disturbed soil samples and 16 core ring samples were collected from five representative profiles. The samples were analyzed in the laboratory for texture, BD, FC, PWP, Soil pH, EC, OC, TN, av.P, av.K, exchangeable bases, free and active iron and CEC. The results showed that the proportions of soil separates varied among profile and depth however, soils were all in clay textural class. The BD varied from 1.02 in the surface profile 1 to 1.25 g.cm-3 in the profile 3. Soil pH ranged from 6.8 to 5.4 in the surface horizons of all profiles with further decrease with depth indicating that the soils in the watershed are slightly acidic to moderately acidic. The OM and TN contents ranged from 2.90 to 5.43 and 0.23 to 0.45% in the surface horizon and they were in the low, low to medium and high categories respectively. The corresponding values for the remaining subsoil horizons were in the low categories. In all cases the contents of these parameters decreased considerably with depths. Available P was below critical values for all profiles and depths except for profiles 1 and 4. Exchangeable K was above critical value in all profiles with increasing trend along with depth of all profiles. Exchangeable Mg varied from 2.47 in surface horizon of profile 3 to 3.98 cmolc kg-1 in the surface horizons of profile 4 and increased with depth in all profiles except in profile 1. The observation with exchangeable K and Mg implies that there is leaching phenomenon in the study area. Ca ranged from 4. 35 cmolc kg -1 in profile 5 to 16.50 cmolc kg -1 in profile 1 with inconsistent trend with depth. The CEC from 18.22 cmolc kg -1 soil in surface horizon of profile 5 to 27.43 cmolc kg-1 soil in the surface horizons of profile 1 indicating they are in the medium to high ranges. But inconsistent trend in CEC distribution was observed with depth in all profiles. Based on the data collected from profile description study and soil physicochemical analytical data and according to FAO-WRD soil classification legend, the soil at Ambukuna watershed were classified as Haplic Nitisols (Endoeutric, humic), Haplic Nitisols (Hypereutric, humic), Haplic Nitisols (Endoeutric) and Haplic Nitisols (Epidystric, Humic). Most of the soil physical and some of the chemical characteristics studied could be ranked as good indicating that the area has high potential for agricultural production.